Effects of a 10-week Nordic hamstring exercise and Russian belt training on posterior lower-limb muscle strength in elite junior soccer players - Rey, E.; Paz-Dominguez, Á.; Porcel-Almendral, D.; Paredes-Hernández, V.; Barcala-Furelos, R.; Abelairas-Gómez, C. (The Journal of Strength and Conditioning Research, 2017)
The purpose of this study was to assess the effect of 2 eccentric hamstring training exercises, Nordic hamstring exercise (NHE) and Russian belt (RB), on lower-limb strength and bilateral asymmetry using the single-leg hamstring bridge (SLHB) test. Forty-seven elite junior soccer players (age 17.7 ± 0.5 years, height 175.3 ± 3.6 cm, body mass 68.1 ± 7.4 kg) were randomized into 1 of 3 groups, the NHE group (n = 16), RB group (n = 15), or the control group (CG) (n = 16). The eccentric training intervention consisted of 27 supervised training sessions over 10 weeks. Within-group analysis showed significant improvements (p < 0.001) in right SLHB (+25.52% for NHE and +18.33% for RB) and left SLHB (+28.92% for NHE and +20.08% for RB) from pretest to posttest in NHE and RB. However, no significant pre-post changes were observed for the CG in any variable. In addition, a significant time effect (p = 0.028) was also observed for NHE in bilateral asymmetry decreasing from pre- to posttest. In the between-groups analysis, significant better results were found in right SLHB and left SLHB, in the NHE group and RB group in comparison with CG. However, there were no differences between the eccentric training groups (NHE vs. RB). The RB seems to be a viable alternative to the NHE to developing posterior lower-limb muscle strength based on SLHB.